1991
DOI: 10.1111/j.1600-0838.1991.tb00279.x
|View full text |Cite
|
Sign up to set email alerts
|

Health, job stress and psychological defense in physically active and inactive subjects

Abstract: The relationships between levels of physical activity and self‐reports of health complaints, job stress and psychological defense were investigated in a broad screening on clerical workers in an insurance company (n= 171). The workers were divided into 4 groups, based on self‐reports of self‐administered leisure physical activity or sports. The highly physically active group (n= 43) had 3 or more sessions of at least 45 min regular physical exercise per week. The moderately active group (n= 31) had 1–2 session… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
1
2
0
1
Order By: Relevance
“…Consistent with previous research, more women than men experienced higher numbers of barriers, and reported health barriers, practical barriers and priority barriers to be of importance (Jaffe et al, 1999; Sternfeld et al, 1999; Artazcoz et al, 2001). It is also consistent with other research that females report more health complaints than men (Grønningsæter et al, 1991). These results probably reflect differences in the life situations of women and men.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with previous research, more women than men experienced higher numbers of barriers, and reported health barriers, practical barriers and priority barriers to be of importance (Jaffe et al, 1999; Sternfeld et al, 1999; Artazcoz et al, 2001). It is also consistent with other research that females report more health complaints than men (Grønningsæter et al, 1991). These results probably reflect differences in the life situations of women and men.…”
Section: Discussionsupporting
confidence: 93%
“…In a Norwegian non-clinical sample ( n = 704), the total defense score was 27.78 (8.5; Endresen, 1991 ), indicating that these data were in the same range as in the present study. Another Norwegian non-clinical sample had total scores in the same range ( Grønningsæter et al, 1991 ). In comparison, a group of normal elderly persons had a total score of 34.90 (SD 10.48) ( Conte and Plutchik, 1995 , p. 188); and a group of non-clinical, healthy adolescents 48.88 (SD 29.77; Conte and Plutchik, 1995 , p. 193), i.e., the young group used more defenses than the adults in our sample and the sample of elderly persons.…”
Section: Discussionmentioning
confidence: 99%
“…Onderzoek laat zien dat werknemers die fysiek actief zijn of een hogere slaapkwaliteit hebben, meer tevreden zijn over hun werk (Grønningsaeter, Christensen, Larsen & Ursin, 1991;Raggatt, 1991). Daarentegen zijn werknemers die roken, alcohol consumeren en een lage slaapkwaliteit hebben, juist minder tevreden over het werk (Alexander & Beck, 1990;Raggatt, 1991;Scott & Judge, 2006).…”
Section: Leefstijl En Gunstige Werkuitkomstenunclassified